Vegetação, biomassa microbiana e características químicas do solo como indicadores de reabilitação de áreas mineradas na Amazônia oriental - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2001)
The studied area is located in Porto Trombetas, municipality of Oriximiná, Northwest of Pará, where bauxite is exploited on plateaus. The study aimed to evaluate the recovery of mined areas Porto Trombetas, as well as obtaining index characteristics of the soil recovery stage in the altered sites. The information on vegetation structure and soil collection was made in 14 sites topographically and landscapely rehabilitated between 1981 and 1994 and at a site on the Yellow Latosol (LA) under disturbed vegetation, taken as reference. Soil samples were collected At depths of 0-2.5; 2.5-10 and 10-20 cm. The results were submitted to the cluster analyzes. The lower levels of carbon, nitrogen and phosphorus in the altered soil, in relation to LA, indicate the need for a higher amount of organic matter and higher biological activity for faster recovery of the altered soils. The characteristics related to the organic matter were better indicators of the stage of surface soil recovery. In depth, one must also take into account the characteristics related to the soil matrix. The carbon and phosphorus of microbial biomass were sensitive indicators of changes in the altered soil.
Keywords: Biomassa Microbiana; Solo - Características químicas; Áreas mineradas; Amazônia oriental; CNPQ::CIENCIAS AGRARIAS